Athlete recruitment: Promoting initial and sustained engagement in Para sport - Baker, J.; Mazhar, A.; Frogley, M. (Talent development in Paralympic sport: Researcher and practitioner perspectives, 2022)
Recruitment, very broadly, reflects the process of onboarding athletes into a sporting program and remains a fundamental challenge for many working in Para sport contexts. However, in resource-limited systems, increasing the efficiency of how individuals are engaged and aligned with available programs is critical. In this chapter, we explore recruitment in Para sport, identifying a range of barriers and challenges for researchers and practitioners in this area. Ultimately, recruitment in Para sport should be about more than simply providing opportunities and the latter section of the chapter focuses on recommendations for improving recruitment initiatives. We conclude by advocating an approach that 'provides as many varied, high-quality opportunities as possible, as often as possible' as a way of improving most, if not all, elements of the Para sport system, from local fan/supporter to Paralympic champion.